2009
DOI: 10.13182/nt09-2
|View full text |Cite
|
Sign up to set email alerts
|

ENDF70: A Continuous-Energy MCNP Neutron Data Library Based on ENDF/B-VII.0

Abstract: Following the release of ENDF/B-VII.0 evaluations, an ACE-formatted continuous-energy neutron data library called ENDF70 for MCNP has been produced at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…We observed that for response positions B1, B2 and C1 -C4 in the PWR GEN III model, a non-negligible contributing channel was through the lower plenum (see Figs. 9,12,14). This can also be seen from Figs.…”
Section: Responses Below the Coresupporting
confidence: 72%
See 1 more Smart Citation
“…We observed that for response positions B1, B2 and C1 -C4 in the PWR GEN III model, a non-negligible contributing channel was through the lower plenum (see Figs. 9,12,14). This can also be seen from Figs.…”
Section: Responses Below the Coresupporting
confidence: 72%
“…As for the PWR GEN II model, the neutron cross-section data were based, where possible, on ENDF/B-VII.1 [12]. The only difference was that thermal neutron S(,) data for hydrogen in light water were based on ENDF/B-VII Release 0 [14] (rather than Release 1 for PWR GEN II [13]).…”
Section: Pwr Gen III With Thick Steel Reflectormentioning
confidence: 99%
“…We provided the element-wise base composition and microscopic absorption cross sections for each element in Table S1 in the Supporting Information. In our MCNP6 simulations, we specified the isotropic composition and used the ENDF70 Continuous-Energy MCNP Neutron Data Library (Trellue et al, 2009), which computes the flux-dependent microscopic cross sections. The microscopic cross sections in Table S1 are for 2.2-km/s neutrons at 293 K (Sears, 1992) and were used only for reporting the value of the macroscopic absorption cross-section parameter throughout our analysis (i.e., it was not used directly in the simulations).…”
Section: Modeled Data Setmentioning
confidence: 99%
“…Simulations of neutron flux in aluminium samples and simulations of proton and deuteron flux in lead samples were performed in Monte Carlo simulation code MCNPX version 2.7 [8]. Neutron data library used for the simulations was ENDF70 [9] and physics models were INCL4.2 [10] + ABLA-KHSv3p [11,12]. Cross sections of above mentioned reactions were calculated by deterministic code TALYS version 1.6 [13].…”
Section: Tab 1: Beam Characteristics Of Thementioning
confidence: 99%